The long noncoding RNA LUCAT1 promotes tumorigenesis by controlling ubiquitination and stability of DNA methyltransferase 1 in esophageal squamous cell carcinoma. (28th March 2018) - Yoon, Jung-Ho; You, Bo-Hyun; Park, Chan Hyuk; Kim, Yeong Jin; Nam, Jin-Wu; Lee, Sang Kil
Abstract: Available targeted therapies for esophageal squamous cell carcinoma (ESCC) are limited; thus, further genetic and epigenetic studies are needed. Recently, many long noncoding RNAs (lncRNAs) have been reported to be involved in various cancers. Here, we investigated whether the lncRNA LUCAT1 was related to the carcinogenesis of ESCC based on previous studies in lung cancer. LUCAT1 was significantly upregulated in ESCC cell lines and cancer tissue compared with normal cells and adjacent normal tissues. LUCAT1 knockdown reduced cell proliferation, induced apoptosis, and upregulated tumor-suppressor genes by reducing DNA methylation in KYSE-30 cells. Moreover, LUCAT1 siRNA reduced DNA methyltransferase 1 (DNMT1) protein levels without affecting transcription. Patients with high LUCAT1 expression had significantly lower survival rates than patients with low LUCAT1 expression. Our results thus suggest that LUCAT1 regulates the stability of DNMT1 and inhibits the expression of tumor suppressors through DNA methylation, leading to the formation and metastasis of ESCC. We identified LUCAT1 as a potential target for drug development and as a biomarker for ESCC. Highlights: We investigated whether the lncRNA LUCAT1 was related to the carcinogenesis of ESCC. LUCAT1 was significantly upregulated in ESCC cell lines and tissues. LUCAT1 modulated cell proliferation, apoptosis, and tumor-suppressor genes in ESCC. LUCAT1 regulated the stability of DNMT1. We identified LUCAT1 as a potential drug target and biomarker for ESCC.